Homeowner Preferences for Wildfire Risk Mitigation in the Alaskan Wildland Urban Interface - Molina, Allen; Little, Joseph; Drury, Stacy; Jandt, Randi (Sustainability, 2021)
Wildfire has become a larger threat to human life and property with the proliferation of homes into the wildland urban interface and warming climate. In this study we explored Alaskan homeowner preferences for wildfire risk mitigation in the wildland urban interface using discrete choice experiments to better understand the drivers of their risk mitigation actions. Estimates of willingness-to-pay for private mitigation actions are increased with wildfire risk reduction for all respondents. Willingness-to-pay for private mitigation is also positively associated with the presence of thinned fuel treatments on nearby public lands, but is estimated to decrease if cleared fuel treatments are present on public lands. Our study concludes that homeowners minimize wildfire risk while maintaining neighborhood amenity values. Additionally, findings suggest that there is an optimal amount of neighborhood participation to motivate individual risk mitigation actions, as well as having a say in the mitigation actions on public lands.